2022
DOI: 10.1080/14786419.2022.2115492
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic compounds and bioactive extract produced by endophytic fungus Coriolopsis rigida

Abstract: Coriolopsis rigida was isolated as an endophytic fungus from the medicinal plant Cochlospermum regium, and their production of secondary metabolites has not yet been investigated. Thus, the endophyte was cultivated on rice solid media to evaluate its ability to produce bioactive compounds and then the chloroform extract was obtained. Two phenolic compounds, tyrosol (1) and a new natural product p-hydroxyphenylacetamide (2), were isolated from the extract. The structures of the compounds were elucidated mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…Phenolic compounds are a class of molecules that have a wide distribution in natural products and have attracted a lot of attention due to their antioxidant and antimicrobial properties [63]. Antioxidant compounds produced by endophytic fungi are usually from the class of phenolic compounds, such as flavonoids and phenolic acids, which corroborates the results found in this study [64][65][66]. Additionally, the infrared spectrum obtained for the active pigmented extract is in accordance with the results of the TLC.…”
Section: Discussionsupporting
confidence: 88%
“…Phenolic compounds are a class of molecules that have a wide distribution in natural products and have attracted a lot of attention due to their antioxidant and antimicrobial properties [63]. Antioxidant compounds produced by endophytic fungi are usually from the class of phenolic compounds, such as flavonoids and phenolic acids, which corroborates the results found in this study [64][65][66]. Additionally, the infrared spectrum obtained for the active pigmented extract is in accordance with the results of the TLC.…”
Section: Discussionsupporting
confidence: 88%
“…In recent years, an increasing interest has been shown in endophytes extract because of its safety and anti-stroke properties. The ability of phenolic compounds to cross blood-brain barrier and neuroprotective property without any side effect was reported previously (Dantas et al, 2022). In this study, we analyzed the impact of phenolic compounds in a rat model of cerebral ischemia injury and we observed that pretreatment of Albino rat with phenolic compound at 10-200 mg/kg/day improved protection against oxidative stress.…”
Section: Discussionmentioning
confidence: 54%
“…They also possess anti-ageing properties, for which they are used in the cosmetic industry [30]. In a recent study, [31] isolated two phenolic compounds, tyrosol and phydroxyphenylacetamide, from the endophytic fungus Coriolopsis rigida obtained from the medicinal plant Cochlospermum regium that showed potent antioxidant activity with an EC50 of 0.33 mg/mL and effective allelopathic activity against the seedlings of Lactuca sativa and Raphanus sativus. Compounds belonging to saponins have been known to show antibacterial, antifungal, antiviral, anti-inflammatory, anticancer, antioxidant, and immunomodulatory effects [32].…”
Section: Biochemical Analysismentioning
confidence: 99%